The Tragedy of Regicide in Interregnum and Restoration Histories of the English Civil Wars - Claire Gheeraert-Graffeuille (Etudes Epistémè)
This article explores the generic proximity between history and drama in the Interregnum and Restoration histories of the English civil wars. It first looks at the way historians – whether on the king’s or on the Parliament’s side – appropriated the ingredients of tragedy in order to structure their narratives of the regicide and characterize their protagonists. Then, it examines the ambivalent use of theatrical emotion in royalist histories. To be sure, stirring up the passions of the readers was an effective way of persuading them of the justness of the royalist cause, but at the same time this use of pathos stood in contradiction with historical impartiality. It would be unfair, however, to consider such a theatrical presentation of history merely as an instrument of political propaganda; on the contrary, historical narratives could serve a truly tragic vision of history, conferring complexity on an act often related in a Manichean way in the 1650s and at the Restoration.